Student worksheets based on teach Ki Hadjar Dewantara on materials volume of cubes and cuboid fifth grade of elementary school - Munjianaha, Lutfiatul; Trisniawati, Trisniawati; Muanifah, Mahmudah Titi; Murniningsih, Murniningsih (Universitas Negeri Malang, 2023)
This study aims to (1) Develop student worksheets based on Ki Hadjar Dewantara Teaching method which is Tri-N (Niteni, Nirokke, Nambahi) with teaching material volume of cube and cuboid. (2) Testing properness, practicability and effectiveness of Student Worksheets. This research using Research and Development method. The model of the development method is ADDIE. This research is limited on the steps of implementation in a minor scale research which has been done in SDN Jogoresan with subject of fifth grade which consist of 19 students. The collecting data technique is using instrument sheet assessment which is validation with using 4 assessment scale, student response questioner and test of student final exam. This research is using analysis technique qualitative and quantitative. The result of this research is: (1) Student worksheets based on Ki Hadjar Dewantara has been generated with material volume of cube and cuboid on fifth grade of elementary school. (2) Gain total validation value form those three expert is 3.47 which can be categorize that student worksheets are “very valid”. (3) Result of student response questioner as a test of practically student worksheets is as much as 3.6 which can be categorize “very practice”. (4) Gain the value average of the class is 87.89 with percentage of completeness 94 percent and can be categorize “very effective”. The conclusion is that the research of student worksheets is successfully valid, practice, and effective.